THE STRATEGY MAPS AND BALANCED SCORECARD DESIGN STUDY OF PT PERKEBUNAN NUSANTARA VII (PERSERO) - , Willy Mulyawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Perkebunan Nusantara VII (Persero) is one of the State-Owned Enterprises (SOE) that Headquarters is in Bandar Lampung, Lampung Province. The company cultivates and processes four commodities i.e., rubber, oil palm, sugar cane, and tea. The roles of the company in developing national economic can be seen from its processed products that contributed to total national products. That roles would not succeed if the company does not formulate and implement strategy very well. Therefore, the company created strategic planning that stated on Rencana Jangka Panjang (RJP) with five year period. RJP is an elaboration of mission statement and company vision. However, the problems arise whether strategic planning stated in RJP 2010-2014 has been well understood by all management at every level or not in order to guarantee that strategy on that period was well implemented. Moreover whether there is a performance measurement to evaluate the strategy implementation or not with its purpose of evaluating and giving feedback. The research answered the problems by designing Strategy Map and Balanced Scorecard framework. Strategy Map creates synergy between strategy and operations by guiding all management at every level in order to implement the strategy. While Balanced Scorecard measures the performance of strategic implementation. The research used source of information that came from primary data and interview using purposive sampling. The research result showed that in financial perspectives there are two strategic objectives i.e., Cost Efficiencies and Effectiveness, and Return Rate. In Customer Perspective, there are Optimum Pricing Strategy, High Quality Processed Product, Product Development, Market Development, Excellent Service, Customer Relationship, and Environment Friendly Products as its strategic objectives. The number of strategic objectives on Internal Business Perspectives are the most among the others namely Effective Cultivation Technology Implementation, Horizontal Integration, Vertical Integration, Crops Productivity Improvement, Strategic Alliances with Similar Business, Crops Area Expansions, Processing Optimalization Capacity, Quality Improvement, Maintain the Stakeholders Interest, New Business Development, Existing Business Development, Waste Management, Land Legal Aspect, and Corporate Social Responsibility. While in the Learning and Growth Perspective there are Competence-based Human Resource Development, Human Resource Productivity Improvement, Human Resource Composition, Enterprise Resource Planning (ERP) Development, Performance Appraisal System Development, Effective Good Corporate Governance, and Corporate Culture Development.